Derangement of the endothelial glycocalyx in sepsis. (3rd February 2019) - Iba, T.; Levy, J. H.
Abstract : Summary: The vascular endothelial surface is coated by the glycocalyx, a ubiquitous gel‐like layer composed of a membrane‐binding domain that contains proteoglycans, glycosaminoglycan side‐chains, and plasma proteins such as albumin and antithrombin. The endothelial glycocalyx plays a critical role in maintaining vascular homeostasis. However, this component is highly vulnerable to damage and is also difficult to examine. Recent advances in analytical techniques have enabled biochemical, visual and computational investigation of this vascular component. The glycocalyx modulates leukocyte–endothelial interactions, thrombus formation and other processes that lead to microcirculatory dysfunction and critical organ injury in sepsis. It also acts as a regulator of vascular permeability and contains mechanosensors as well as receptors for growth factors and anticoagulants. During the initial onset of sepsis, the glycocalyx is damaged and circulating levels of glycocalyx components, including syndecans, heparan sulfate and hyaluronic acid, can be measured and are reportedly useful as biomarkers for sepsis. Also, a new methodology using side‐stream dark‐field imaging is now clinically available for assessing the glycocalyx. Multiple factors including hypervolemia and hyperglycemia are toxic to the glycocalyx, and several agents have been proposed as therapeutic modalities, although no single treatment has been proven to be clinically effective. In this article, we review the derangement of the glycocalyx in sepsis. Despite the accumulated knowledge regarding the important roles of the glycocalyx, the relationship between derangement of the endothelial glycocalyx and severity of sepsis or disseminated intravascular coagulation has not been adequately elucidated and further work is needed.